2003
DOI: 10.1021/jo034070a
|View full text |Cite
|
Sign up to set email alerts
|

General Patterns in the Photochemistry of Pregna-1,4-dien-3,20-diones

Abstract: The photochemistry of six pregna-1,4-dien-3,20-diones has been compared and found to involve both the cyclohexadienone moiety in ring A and the isolated ketone at C-20. The two reactions take place proportionally to the fraction of light absorbed by each chromophore. The cross-conjugated ketone absorbs predominantly or exclusively at both 254 and 366 nm and undergoes the "lumi" rearrangement to bicyclo[3.1.0]hex-3-en-2-one. The quantum yield of the reaction diminished somewhat with increasing lambda(exc), e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…This lead to a different photochemistry observed by the direct excitation of ketone chromophore. Albini et al 8,9) have demonstrated non-communicating reaction paths in some pregna-1,4-diene-3,20-dione. Since many steroidal drugs are commonly used and several reports on their phototoxic effects have been reported, [10][11][12][13] it was of interest to extensively study the aspect of competition between chemical reactions of the separated excited moieties incorporated in the rigid skeleton of the steroids.…”
mentioning
confidence: 98%
“…This lead to a different photochemistry observed by the direct excitation of ketone chromophore. Albini et al 8,9) have demonstrated non-communicating reaction paths in some pregna-1,4-diene-3,20-dione. Since many steroidal drugs are commonly used and several reports on their phototoxic effects have been reported, [10][11][12][13] it was of interest to extensively study the aspect of competition between chemical reactions of the separated excited moieties incorporated in the rigid skeleton of the steroids.…”
mentioning
confidence: 98%
“…Glucocorticosteroids pregna-1,4-dien-3,20-diones [24] betamethasone and its esters [25,26] betamethasone-17 valerate [27] mometasone furoate [28] hydrocortisone 21-acetate [29] prednisolone [30] fluocinolone 16,17-acetonide [31,32] desonide [33,34] Retinoids vitamin A [35] tretinoin [36][37][38][39][40][41][42][43][44] isotretinoin [36,37,45] adapalene [46,47] tazarotene [48] Antifungal drugs clotrimazole [49,50] bifonazole [51] itraconazole [52,53] terbinafine [54] Non-steroidal antiinflammatory drugs piroxicam [55][56][57] naproxen [58][59][60][61] diclofenac [57,58,62] ketoprofen [63][64][65][66] ibuprofen …”
Section: Drug Class Active Pharmaceutical Ingredientmentioning
confidence: 99%
“…This reaction was reported for prednisolone, whose spectrum and k max (242 nm) are similar to desonide. In some cases, another possible reaction involves the cleavage of C17ÀC20 or the hydrogen abstraction from the 18-methyl group 39 . According to Moore 40 , the spectrum of a drug molecule is usually broad, and any overlap of the absorption spectrum with the output of the photon source colliding with it has the potential to start the photochemical change.…”
Section: Photostability Studymentioning
confidence: 99%